(untitled) (GEON Journal (Management, Organizations and Business), 2017)
Corporate Governance refers to the wapiti’s exercised power in the company, and this power is attributed to managers, is about them that support the development of business activity, as they are called to define the strategy corporate and run. However, the behavior of managers can be influenced by various incentives that lead them to advance a for management to social interests, why measures are needed to proper lee orient the role of managers in the company. This study is a phase of a macro project being developed in framework of the sustainability of family businesses (EF), one of it sadisms to know who has done research on them, what the issues are more elaborate, labor impact generated in Colombia, styles of governance and know what the academic profiles of the managers of these businesses are. Identify the styles of governance in EF in the northern region of Santander, will enable researchers to generates scientific know ledge about a subject that today worldwide has strength andesine the great business schools, as itisthe case University of Navarra in Spain and have a the ore tical basisforfuture studies are made to this environment; in the form of narrativestudyitseeks to consolidate the history of the company sunder study and able to fulfill the objectives.